A calculation of optimal plan of the use of different models of trolleybuses is on routes of a municipal transport network (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
Work is sanctified to development of optimization model of the effective use of present at the enterprises of electric transport brands of trolleybuses on the rout network of city after spreadsheets (on the example of park of trolleybuses in Lutsk).The task of increase to efficiency of work of public passenger transport can be decided or due to updating of transport vehicles, or due to the increase of efficiency of work of present rolling stock. But, to bring down the charges of enterprises on implementation of a transport work, it is necessary to perfect going near her planning, and, as a result of it, to provide the decline of prime price of transportations and improvement of quality of service.For providing of the most effective transport maintenance of population from passenger transportations, organization of travelling motion, it is necessary, that a transport system answered the necessities of city most optimally. There are two ways of increase of such efficiency: or increase of carrying capacity of a municipal transport network, or rational use of existent network and present rolling stock for carrying passengers.The first decision entails large material expenses on the reconstruction of transport knots and highways. The second direction is rationalization of the use of existent transport systems and optimization of processes of redistribution of loading both on a transport network and on the different types of transport vehicles that carry out passenger transportations.In this publication, executed attempt to go round contradiction between theoretical models and real possibilities of a transport enterprise in relation to the effective use of present park of trolleybuses on the routes of city and rapid dynamic count of optimal decisions. Actuality of work consists in development of simple and effective methods of optimization of work of present rolling stock of trolleybuses for carrying passengers on municipal routes.For creation of model of optimization, analysed routes of a municipal transport network of Lutsk and the analysis of present park of transport vehicles of LPЕ is carried out, him functional and technological possibilities for providing of a transport demand of population.Raising of task of minimization of objective function of charges is offered for the optimal plan of distribution of trolleybuses on routes. The built model and worked out algorithms of her introduction are in spreadsheets.The worked out algorithms and programmatic realization of bringing of limitations of relative order are at the use of different models of trolleybuses on routes. It provided the calculation of a number of possible plans of transportations in the process of design. Such plans it is in-process suggested to name rational plans, id est locally optimal at these limitations.Keywords: optimization model, transport network of city, park of electric transport, transport demand of population, limitation of relative order.